REGULATION OF NON SMOKING AREAS IN LOCAL GOVERNMENT REGULATION - Suryani, Danu; Suhartini, Endeh (DERECHTSSTAAT, 2018)
ABSTRACTÂ Non Smoking Area (NSA) is a policy that is made considering that cigarettes are a type of addictive substance which if used can cause harm to the health of the individual or to the surrounding community. Certainly at a glance smoking in a public place does not look like a crime, different from pickpocket, robbery, and other violent crimes, but exposure to cigarette smoke can affect the incidence of disease and even kill all people even. Ironically, passive smokers carry more risk than active smokers or perpetrators. On the other hand public places are considered as free expression areas including smoking. Therefore, the central government up to the regional government stipulates and implements the NSA Policy. The study carried out in Bekasi City by conducting the Normative Juridical Study, Jurisdiction of Sociology, Philosophical Juridical Study andÂ  Juridical Comparative Study (Comparative Research of Law), this study produced a concept of regional regulation that can be scientifically used in Bekasi City.